Age-Related Clinical Presentation of MOG-IgG Seropositivity in Israel - Brill, Livnat; Ganelin-Cohen, Esther; Dabby, Ron; Rabinowicz, Shira; Zohar-Dayan, Efrat; Rein, Netaniel; Aloni, Eyal; Karmon, Yuval; Vaknin-Dembinsky, Adi (Frontiers in Neurology, 2021)
Introduction: Myelin oligodendrocyte glycoprotein (MOG) antibody disease (MOG-AD) has been recognized over the past 10 years as a distinct inflammatory, demyelinating disease of the central nervous system (CNS). The antibodies against MOG are found mostly in patients with optic neuritis (ON), acute disseminated encephalomyelitis (ADEM) and aquaporin-4 antibody (AQP4-IgG)-seronegative neuromyelitis optica spectrum disorders (NMOSD). However, data on the disease course and disability outcomes of these patients are scarce. Aim: To describe clinical and paraclinical features associated with MOG antibodies (abs) in a cohort of patients in Israel, and to assess baseline prognostic features of MOG-ab-associated diseases after a first acute demyelinating event. Methods: MOG antibodies were identified in serum using a cell-based assay, and clinical data were collected from the patients' medical records. Results: Of 683 patients with demyelinating diseases tested for MOG-abs, 53 were positive (7.7%), with ON the most common presenting phenotype (68%). The age range of MOG-IgG seropositive patients was 1-66 years, with increased prevalence in children (19% compared to 6.7% in adults) (p<0.01). The highest prevalence of seropositivity was observed in children aged younger than 10 years (25.5%), followed by those aged 31-40 years (16.6%). Conclusions: MOG-antibody disease is a distinct autoimmune disease that occurs at all stages of life with a significantly higher prevalence in children; the main clinical presenting phenotype in the entire cohort is ON and young children most often presented with ON or ADEM. Our data highlight the need for repeated evaluation of MOG-abs predominantly in pediatric patients and in those between 31 and 40 years of age, with acquired CNS demyelination.